Athlete vs. mathlete : double dribble - Mack, W. C., 1972- (Bloomsbury, 2013)
Fraternal twins Russ and Owen's domination of the seventh-grade basketball team falters when Mitch and Marcus Matthews, identical twins, arrive and prove their skill on the court and in the classroom.